Lead Shield and Protective Cap Reduce Operator Radiation Exposure by >75% - Rizzo, Toni (MD Conference Express, 2014)
Radiation exposure by interventional cardiologists has led to concern about the risk of malignancy. The objective of the RADIATION PROTECT trial [NCT02128035] was to evaluate the efficacy of a pelvic lead patient drape and a nonlead surgical cap for reducing radiation exposure in interventional cardiologists.